Death Audit of Swine Flu Cases in Surat City - Hiren Jadawala; Khushbu Patel; Rachna Prasad; Manan J Patel; Jayesh J Rana; RK Bansal (Medsci Publications, 2015)
Introduction: Evaluation of medical care in retrospect through qualitative analysis of clinical records, including analysis of hospital services is a simpler way to look into the meaning of Death Audit. Late presentation at hospital and having co-morbid conditions were commonly observed to be associated with poor patient outcome. Objective of the study was to assess the epidemiologic characteristics & high-risk profiles among reported deaths with H1N1 influenza in Surat city. Method: Death audit of 47 swine flu positive cases were carried by household visit and checking medical records from respected hospitals of Surat Municipal Corporation area. Results: Deaths were higher among age group of 40-60 years and above and female population. Out of total 47 deaths, only 20 swine flu positive patients had reported to hospital within 48 hours after onset of signs & symptoms. More than 83% swine flu death patients had not taken oseltamivir within 48 hours after onset of signs & symptoms. Diabetes and hypertension, IHD were co morbid condition and pregnancy was associated condition with H1N1 fatality. Conclusion: Mortality was higher in patient having co-morbid conditions like hypertension, diabetes, pregnancy, thyroid disorder. Longer interval between onset of signs and symptoms to diagnosis and initiation of oseltamivir may be the possible reason for higher mortality during swine flu epidemic 2015.